Law and Democracy in Neil MacCormick's Legal and Political Theory: The Post-Sovereign Constellation - Menéndez, Agustín José (Law and philosophy library, 2011)
This volume offers a collection of articles by leading legal and political theorists. Originally intended as a celebration of MacCormick's work on the occasion of the completion of the four-volume series on Law, State and Practical Reason, it has turned into a homage and salute after MacCormick's passing. Cast in MacCormick's reflexive spirit, the book presents a critical reconstruction of the Scottish philosopher's work, with the aim of revealing the connections between law and democracy in his writings and furthering his insights in each specific field. Neil MacCormick made outstanding contributions to the understanding of law and democracy under conditions of pluralism. His institutional theory of law has elucidated the close connection between the normative character of law as a means of social integration and legal social practices. This has produced a synthesis of the key insights of the legal and political theories of Kelsen, Hart, Alexy and Dworkin, and has broken new ground by undermining the 'monolithic' and 'nation-state' centered character of standard legal theories.
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Rechtsphilosophie; MacCormick, Neil